Integration of Ethical and Emotional Values in Curriculum Development at Madrasah Aliyah - Gusma Afriani (EDUJAVARE: International Journal of Educational Research, 2026)
Madrasah Aliyah education increasingly requires curriculum development that integrates intellectual competence with ethical maturity and emotional competence. However, ethical values are often explicitly stated in curriculum documents, while emotional development remains implicit in classroom interactions and institutional culture. This study aims to analyze how ethical and emotional values are integrated into Madrasah Aliyah curriculum development, including their forms, implementation mechanisms, supporting conditions, and challenges. The study employed a qualitative approach with an exploratory case study design. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving school leaders, curriculum personnel, teachers, and selected students. Data were analyzed thematically through deductive and inductive coding, supported by source and method triangulation. The findings show that ethical values are more formally institutionalized, whereas emotional competencies are predominantly developed through teacher modeling, collaborative learning, reflection, and the hidden curriculum. Meaningful integration occurs when normative, pedagogical, and cultural dimensions are aligned. The study concludes that ethical values provide normative direction, while emotional competencies enable students to enact those values through self-regulation, empathy, and responsible decision-making. Its contribution is an integrative curriculum perspective positioning ethical and emotional development as mutually reinforcing dimensions of curriculum architecture rather than separate character-building programs across diverse contemporary Islamic secondary education contexts.